Elmo's world food, water & exercise! - SMV Enterprises ([United States] : Sony Music Video, 2005)
Join Elmo as he explores why food, water and exercise are essential parts of our life! With Elmo, preschooler will learn about foods from around the world, dip into deep water and stay healthy and strong with exercise!
Title from container.
MPAA rating: Not rated.
DVD, region 1; Dolby Digital.
Keywords: Food -- Juvenile films; Water -- Juvenile films; Exercise -- Juvenile films; Children's films